Implementasi Ṭarīqah Intiqāiyah dalam Pembelajaran Bahasa Arab Untuk Meningkatkan Hasil Belajar Bahasa Arab Siswa Kelas VI MI PSM Walikukun Desa Bangunrejo Kecamatan Sukorejo Kabupaten Ponorogo Tahun 2021 - Siti Munawaroh; Lisma Meilia Wijayanti; Nanik Setyowati (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The purpose of this study is to describe the role, implementation, and constraints of Ṭarīqah Intiqāiyah in learning Arabic for class VI MI PSM Walikukun. The method used in this research is descriptive qualitative. The object or population in this study were 15 students of class VI MI PSM Walikukun. In this study, the primary data selected by the authors were interviews with Arabic teachers for grade VI MI PSM Walikukun and observations of the learning process. Secondary data sources in this study were lesson plans, grade transcripts and observations of the Arabic language learning process of class VI MI PSM Walikukun. Data collection techniques are carried out through observation, interviews, and documentation. Meanwhile, data analysis was carried out using the Miles and Huberman approach. The results of this study indicate that the implementation of Ṭarīqah Intiqāiyah in learning Arabic for class VI MI PSM Walikukun can be considered to be going well, because it is adapted to the abilities and needs of students and the capacity of the Arabic language teacher. Even though the combined steps and methods are not in accordance with the steps exemplified by Acep Hermawan, the use of the Ṭarīqah Intiqāiyah is considered well implemented because the Ṭarīqah Intiqāiyah itself is flexible.